A Systematic Review of Triphala Churna: A Focus on Ingredient Synergism and its Implications for Human Health - Mayuresh Joshi,; Prerna Khanchandani, (International Journal of Scientific Research in Science and Technology, 2024)
Triphala Churna, a revered Ayurvedic formulation, has gained global recognition for its multifaceted health benefits. This review delves into the traditional uses and modern scientific evidence supporting the therapeutic potential of Triphala Churna and its constituent fruits: Amalaki (Emblica officinalis), Bibhitaki (Terminalia bellirica), and Haritaki (Terminalia chebula). Amalaki, rich in vitamin C and antioxidants, exhibits potent anti-inflammatory and immune-boosting properties. Bibhitaki possesses anti-inflammatory, antimicrobial, and hepatoprotective actions. Haritaki demonstrates laxative, anti-diabetic, and anti-inflammatory effects. These synergistic interactions among the ingredients contribute to the wide range of pharmacological activities observed with Triphala Churna, including improved digestion, enhanced immunity, antioxidant protection, and support for various chronic diseases. The growing body of scientific research validates the traditional claims of Triphala Churna, solidifying its position as a valuable therapeutic agent in the realm of herbal medicine. As interest in natural and integrative approaches to healthcare continues to rise, Triphala Churna holds immense potential to contribute to global wellness by offering a safe and effective alternative or complementary therapy for various health conditions. This current review comprehensively summarizes the therapeutic potential of Triphala Churna and its ingredients, providing a valuable foundation for future research and clinical applications.
Keywords: Triphala churna; Review Article; Therapeutic potential; uses; Ingredients